Van Dijk Perspective on Jokowi's Political Dynasty Issue: an Appraisal Analysis on Kompas Media News - Ibnu Hudzaifah Hanief; Dhiva Alfath Al Dhani; Andhika Reyfadillah Septiana; Ren Sherlaine B. Simbilon; Mary Rose Damianne Caybot (Research and Innovation in Social Science Education Journal (RISSEJ), 2024)
This essay reveals the ideology and power or political power expressed in Prabowo's news. The data of this research is obtained from one of the most famous online media, Kompas. Based on Van Dijk's theory, the reaction conveyed or shown is part of information filtering, knowledge, and context analysis. Context analysis is usually the most influential, the context outside the text, needs to be analyzed carefully and sensitively. the analysis used is textual meaning. Apply analysis of the qualitative textual systemic functional linguistics method of research, particularly the use of appraisal according to Martin and White. Based on the analysis, it can be concluded that. The purpose of this article is to explore the key ideas put forth by Kompas media, presented in their actual form, and to present Prabowo Subianto's opinions regarding the political dynasty he supports in relation to his presidential bid. The incumbent President of the Republic of Indonesia, Joko Widodo, is the father of Gibran Rakabuming Raka, the vice-presidential candidate he is fielding.